Superstack Nostalgia: Miners and Industrial Heritage in Sudbury, Ontario - King, Adam D. K. (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
The growth of industrial tourism and heritage has both fascinated and frustrated scholars of deindustrialization. Frequently, workers and class conflict are obscured in or expunged from the official narratives of industrial heritage. This article makes an original contribution to research on deindustrialization and industrial heritage through fieldwork in Sudbury, Ontario – a region that has seen a decades-long process of industrial restructuring. The article draws on 26 qualitative interviews with current and retired nickel miners and analyzes workers’ reflections on local mining history. It examines how workers understand the foreign takeover of the mines, job loss, and the transformation of Sudbury’s regional economy away from blue-collar industrial employment. The article then explores the growth of regional tourism based around the mining sector, looking particularly at Dynamic Earth, an attraction that teaches visitors about the history of nickel mining through guided tours of a closed mine. On the one hand, workers critique what they see as an obfuscation of class conflict in industrial heritage, while on the other hand, they experience these sites as confirmation of the historic contributions nickel miners have made to Sudbury and the surrounding region.